2007
DOI: 10.1139/f07-069
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and survival of Northeast Pacific Ocean fish stocks: temporal trends, covariation, and regime shifts

Abstract: Two measures of productivity for fish stocks (recruitment and stock–recruit residuals) within two large marine ecosystems (Gulf of Alaska and eastern Bering Sea – Aleutian Islands) showed significant positive covariation within several groups of species and significant negative covariation between certain others. For example, stock–recruit residuals of gadids (Gadidae) in the Bering Sea were inversely related to those of shelf flatfishes (Pleuronectidae), suggesting that environmental forcing affects these gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 38 publications
1
46
1
Order By: Relevance
“…This is somewhat unexpected and seems to contradict earlier work by e.g. Mueter et al (2007), who pointed out that climate may induce persistent change in recruitment dynamics. Our results, in contrast, indicate that climate generally is not the main driver behind the long-term (as opposed to inter-annual) changes in juvenile survival or that the temperature measurements fail to capture the key climate changes.…”
Section: Recruitment Per Ssb Changes With Long-term Changes In Tempercontrasting
confidence: 85%
See 1 more Smart Citation
“…This is somewhat unexpected and seems to contradict earlier work by e.g. Mueter et al (2007), who pointed out that climate may induce persistent change in recruitment dynamics. Our results, in contrast, indicate that climate generally is not the main driver behind the long-term (as opposed to inter-annual) changes in juvenile survival or that the temperature measurements fail to capture the key climate changes.…”
Section: Recruitment Per Ssb Changes With Long-term Changes In Tempercontrasting
confidence: 85%
“…The importance to recruitment of the different mechanisms may change over time, as a mortality factor operating at an early life stage may or may not be overshadowed by mortality factors operating at later life stages. Mueter et al (2007) emphasized that recruitment can be affected by predation; therefore, 'environmental'effects on productivity include changes in abundance of important predators, regardless of whether these were caused by environmental variability, fishing, or other factors. For instance, Stige et al (2013, this volume) found changing relevance of different environmental factors (including sea temperature and abundance of cod age 3 to 6 yr) for predicting recruitment of the Northeast Arctic cod and the North east Arctic haddock in the Barents Sea.…”
Section: The Stock-recruitment Relationship Is Enhanced By Including mentioning
confidence: 99%
“…However, for some stocks or species, there have also been dramatic increases in catch (or abundance) that cannot be easily attributed to changes in the management of these fisheries, and such increases may be related to climate change (Figure 1). There appears to be compelling evidence of a speciesspecific response to climate change (Spencer and Collie 1997;McFarlane et al 2000;Lehodey et al 2006;Mueter et al 2007;Osgood 2008), and this study provides a broader perspective of this important issue. In addition to the various socioeconomic effects, biological changes at the population level may well influence genetic diversity, interactions with other species, and a species' ability to adapt to future environmental stresses.…”
Section: Fish Catch Synchrony With Climate Regime Shifts 163mentioning
confidence: 79%
“…(a) Meta-analysis of marine fisheries data Although our model predicts MI on maximum reproductive rate that increases with RLS (figure 1), population dynamics in the wild are shaped by a suite of interacting physical and biological factors (Hilborn & Walters 1992;Trippel 1995;Mueter et al 2007) that could overwhelm MI and limit their relevance to management.…”
Section: Evidence For MI On Reproductive Ratementioning
confidence: 99%
“…Third, long-term climatic conditions (regimes) can dominate the recruitment dynamics of many marine fish stocks by causing persistent and geographically pervasive changes in the carrying capacity of a marine environment (Mueter et al 2007). However, for climate regimes to explain the positive relationship between a g 0 =a d 0 and RLS, they must have closely coincided with periods of relatively high and low fishing mortality, and affected long-lived species more strongly than short-lived ones.…”
Section: Evidence For MI On Reproductive Ratementioning
confidence: 99%